On a Gauss-Kuzmin-Type Problem For a Generalized Gauss-Kuzmin Operator - Chrysoula Ganatsiou (International Journal of Mathematics and Mathematical Sciences)
A generalized limit probability measure associated with a random system with complete connections for a generalized Gauss-Kuzmin operator, only for a special case, is defined, and its behaviour is investigated. As a consequence a specific version of Gauss-Kuzmin-type problem for the above generalized operator is obtained.